The Impact of General Anesthesia on Postoperative Cognitive Dysfunction Using Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment–Indonesian Version (MOCA-Ina) in Geriatric Patients - Mardila, Farhana; Irina, Rr Sinta; Wijaya, Dadik W.; Yunanda, Yuki (Journal of Neuroanaesthesiology and Critical Care, 2025)
Postoperative cognitive dysfunction (POCD) is a serious issue in geriatric patients undergoing general anesthesia procedures. Perioperative cognitive function assessment is vital for selecting anesthesia techniques in elderly patients.This pretest–posttest cohort study assessed the effect of general anesthesia on POCD in geriatric patients ≥60 years from three government hospitals in Medan. Cognitive function was measured using the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment Indonesian version (MoCA-Ina) tests 1 day before and 3 days after surgery.Thirty-six patients were included, with an average age of 65.42 ± 4.23 years. The majority were female (52.8%), with a high school education (50%), and worked as farmers/laborers (25%). The average surgery duration was 150 ± 39.93 minutes. A significant decrease in MMSE (26.83 ± 1.5 vs. 26.58 ± 1.44) and MoCA-Ina (27.28 ± 1.06 vs. 27.05 ± 1.01) scores was observed 3 days postoperatively (p < 0.05), with high correlation between the two tests (97.2%; p > 1.00).General anesthesia significantly affects POCD in geriatric patients based on MMSE and MoCA-Ina scores.
Keywords: general anesthesia; geriatric; MMSE; MoCA; POCD